2008
DOI: 10.1097/prs.0b013e3181882129
|View full text |Cite
|
Sign up to set email alerts
|

Patient Self-Report of Disability of the Upper Extremity following Osteocutaneous Radial Forearm Free Flap Harvest

Abstract: Objective reductions in wrist, forearm, and/or thumb range of motion are frequent after harvest of an osteocutaneous radial forearm free flap. Wrist range of motion has the greatest impact on patient self-report of disability and may in a minority of patients be perceived as causing a clinically significant disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…Studies have variously reported 25% of patients with forearm disabilities, 4 none or minimal disability in the majority of patients (58.3%), 8 and moderate or extreme dysfunction in most cases (exact data not available). 5 This between-study variation may be due to differences in sample size.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies have variously reported 25% of patients with forearm disabilities, 4 none or minimal disability in the majority of patients (58.3%), 8 and moderate or extreme dysfunction in most cases (exact data not available). 5 This between-study variation may be due to differences in sample size.…”
Section: Discussionmentioning
confidence: 99%
“…9,[21][22][23][24] Some studies have focused on wrist mobility, but the effect of RFF flap harvest on this parameter is unclear. [7][8][9][10] In addition, it has been shown that objective measurements do not accurately reflect the patient's experience. 4,6 This may be because the majority of RFF flaps are harvested from the non-dominant arm, and the reduction in wrist motion was not severe enough to impact significantly on daily life.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations